Attached Macroinvertebrates Inhabiting Marine Plastic Debris from the Beach and Port Areas of the Southern Sea of Korea - Gwan Hee Han; Sang Lyeol Kim; Su Min Kang; Hyung-Gon Lee; Ok Hwan Yu (Journal of Marine Science and Engineering, 2023)
The increasing amount of marine plastic debris (MPD) poses risks of ingestion, entanglement, and transport of alien species. A new ecosystem called the “plastisphere” is currently being studied, but relevant research on it is limited. In this study, we analyzed the frequency of appearance of macroinvertebrate species on MPD. Macroinvertebrates attached to MPD were collected once every three months from March to December 2021 in eight regions. MPD in the form of aquaculture and fishing gear was detected most frequently during the study. In total, two phyla, 14 orders, 19 families, and 41 species of attached macroinvertebrates were detected during the study. There were more attached macroinvertebrate species, and they were more frequent, on fishing/aquaculture MPD (sea origin) than packaging MPD (land origin). Most fishing/aquaculture MPD is made of softer or rougher materials than packaging MPD and has a longer exposure time in the sea. In particular, the alien species Mytilus galloprovincialis was found on all longer-exposure MPD. These findings suggest that the macroinvertebrates attached to MPD are affected by the duration of exposure to the water and the characteristics of the MPD material. Therefore, in the future, fishing/aquaculture MPD could be used as an indicator for monitoring MPD-attached organisms.